DETERMINANTS OF PUBLIC AWARENESS TO PAY TAXES THROUGH WORK EFFECTIVENESS AS A MEDIATION VARIABLE - Budiarti, Retno; Andre Dwijanto Witjaksono; Anang Kistyanto (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2024)
Phenomenon/Issue: Local government and village head leadership play an important role in increasing public awareness of paying taxes, but work effectiveness as a mediating variable has not been widely explored. Purpose: This research aims to analyze the influence of government policy and village head leadership on public awareness of paying taxes, with work effectiveness as a mediating variable. Novelty: This research adds work effectiveness variables as mediators to deepen understanding of how government policy and village head leadership can influence people's awareness of paying taxes. Research Methods: Quantitative research using a survey approach was carried out in Karangrejo Village, Karangrejo District, Magetan Regency. Data was collected through questionnaires filled out by respondents who were residents of Karangrejo Village. Results: The results of the study show that government policy and village head leadership have a significant effect on people's awareness of paying taxes. Work effectiveness was found as a mediating variable that strengthens this influence. Research Contributions: This research provides insight into the importance of transparent government policies and responsive village head leadership to increase work effectiveness and public awareness in paying taxes, which will ultimately have a positive impact on increasing local tax revenues